Cemento-ossifying fibroma of the jaw: A case report - Moara GP. Yudha; Wenny Yulvie; Vera Julia (Journal of Dentomaxillofacial Science, 2021)
Objective: The purpose of this case report is to evaluate the treatment plan for the following patients. The definite diagnosis of these lesions requires the integration of their clinical, radiological and histological characteristics. Methods: For 8 years ago, a 52-year-old female patient initially felt an increase in the mouth of the left lower jaw. The lumps are initially the size of a marble and then expand like a ping-pong ball. The lumps are painless. Before the mass, there was no history of trauma in this area. There is no history of fever and no history of weight loss. The patient underwent a biopsy of the left mandible at Dr. Cipto Mangunkusumo National Central Public Hospital in September 2019. Results: Cemento ossifying fibroma. The lumps in the cheek gums extend to the lingual area of ​​teeth 35-37, the size is 6x5x4cm, the texture is hard, the surface is smooth, the boundary is not clear, not fixed, there is no tenderness, and the color and temperature are the same as the surrounding tissues. The lump does not bleed easily, and there is no discharge of pus or blood. The patient's treatment plan was to perform a segmental mandibular resection with a 2.4 mm reconstruction plate. Conclusion: The treatment planning for segmental mandibulectomy in general anesthesia is one of the right treatment options. Choosing a submental submandibular approach to the surgical procedure can provide easy access and visualization during surgery.